MENYELAMI DINAMIKA AKUNTANSI SYARIAH KONTEMPsORER DI INDONESIA - Mochamad Rezza Ramadhan; Najwa Jannatul Ma’wa; Muhamad Farhan Nugraha; M. Masrukhan (Cahaya Ilmu Bangsa, 2024)
This article discusses the dynamics of Sharia accounting in Indonesia in contemporary times. The study aims to learn about the development of Sharia accounting in Indonesia, the challenges faced, and the efforts made to address them. The method used in this research is a library study. The results of the research show that Sharia accounting in Indonesia has undergone rapid development along with the development of Sharia banks and other Islamic business institutions. However, there are still some challenges faced in the development of Sharia accounting in Indonesia, such as a lack of understanding of the principles of Sharial accounting, lack of expertise, and lack of support from the government. Therefore, efforts are needed to overcome these challenges, like improving understanding of sharia principles, improving the quality of the staff, and providing government support. Implications-Implications are that the value of today's conventional modern accounting must be redefined to bring stakeholders more benefits and create less harm to society. The reporting value should provide information to stakeholders about the current state of the real situation and provide a meaningful solution to improving the welfare of the stakeholder.